Reaksi Pasar Terhadap Reentry Perusahaan Pada Indeks Saham Syariah Indonesia - Roviah, Siti; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
An index as an indicator to observe the movement of the price of securities. When shares of a company announced entering specific index, it is considered a sign that the company deserves more confidence from investors. Abnormal return occurs due to abnormal transactions throughout the event period. Selection is based on the length of the event period the number of observations and avoid the confounding effect. This study aimed to determine the reaction of the market along announcement of changes in the composition of the index. If there are differences, the market reaction to changes in the composition can be categorized as an announcement containing the information. Events throughout the 21-day period with a sample of companies that reentry amounted to 72 companies and 78 events reentry. Hypothesis testing using two different test paired samples (paired sample t-test). Hypothesis testing results showed no significant difference in abnormal returns before and after events reentry. Keywords : Abnormal Return, Market Reaction, Reentry